Decreased incidence of pertussis in young adults after the introduction of booster vaccine in military conscripts: Epidemiological analyses of pertussis in Finland, 1995–2015. Issue 39 (18th September 2017) - Zöldi, Viktor; Sane, Jussi; Nohynek, Hanna; Virkki, Maria; Hannila-Handelberg, Tuula; Mertsola, Jussi
Highlights: Finnish recruits (98% males) have received acellular pertussis booster vaccination since July 2012. This was followed by a decrease of pertussis incidence in the respective age categories among both males and females. A general conscript dose could be regarded as additional pertussis immunization strategy. Abstract: Introduction: In 2005, in Finland, the whole-cell pertussis vaccine was replaced by acellular given at 3–5–12 months, and boosters at 4 and 11–15 years of age. From July 2012, military conscripts have been offered a pertussis booster dose. Conscription is mandatory for Finnish men, and >95% were 19–21 years old when enrolled during 2012–2015. We describe the epidemiology of pertussis in Finland during 1995–2015, and show the indirect effect of the booster in conscripts on pertussis incidence in the Finnish population. Materials and methods: We extracted data on laboratory confirmed notified pertussis cases from the National Infectious Diseases Register. We calculated annual incidence using as denominator population data and incidence rate ratios (IRR) using Poisson regression. Results: The overall pertussis incidence peaked in 2004 (31/100, 000) and was lowest in 2015 (3.0/100, 000), with 66 reported cases in <3 months infants in 2004 versus 6 in 2015. The majority of the cases were female (59%) with a male-to-female case ratio of 1:1.5. Cases were spread throughout the year with highest incidence during August-February. Among the 19- to 21-year-olds in the general population, incidence decreased from 49/100, 000 in 2011 to 0.51/100, 000 in 2015 (IRR = 0.01; 95%CI, 0.00–0.16). Among the same age group, comparing the 3.5-year period before and after July 2012, incidence decreased from 33/100, 000 to 5.3/100, 000 (IRR = 0.16; 95%CI, 0.06–0.40) in males and from 16/100, 000 to 5.0/100, 000 (IRR = 0.31; 95%CI, 0.11–0.84) in females. Conclusions: Implementation of the pertussis booster dose in Finnish military conscripts was followed by a significant decrease in pertussis incidence both among the 19- to 21-year-old males and females, possibly reflecting herd immunity effect. Together with booster doses in adolescents this has resulted in low incidence in the whole population including infants. Our results support the implementation of the booster dose for conscripts. We recommend continuing monitoring pertussis epidemiology to optimize pertussis vaccination strategies in Finland.